Предмет: Алгебра,
автор: АлёнКа092799
помогите решить пожалуйста срочно
Приложения:
Ответы
Автор ответа:
0
a(2;3;0) b(0;-3;-2) c(1;1;-1)
a-(1/2)b+c=(2;3;0)-(1/2)*(0;-3;-2)+(1;1;-1)=(2;3;0)-(0:2;-3:2;-2:2)+(1;1;-1)=(2;3;0)-(0;-1,5;-1)+(1;1;-1)=(2-0+1;3-(-1,5)+1;0-(-1)+(-1))=(3;5,5;0)
A(1;-4;7) B(5;6;-5)
|AB|=√(x₂-x₁)²+(y₂-y₁)²+(z₂-z₁)²=√(5-1)²+(6-(-4))²+((-5)-7)²=√16+100+144=√260=√4*65=2√65≈16,12
a-(1/2)b+c=(2;3;0)-(1/2)*(0;-3;-2)+(1;1;-1)=(2;3;0)-(0:2;-3:2;-2:2)+(1;1;-1)=(2;3;0)-(0;-1,5;-1)+(1;1;-1)=(2-0+1;3-(-1,5)+1;0-(-1)+(-1))=(3;5,5;0)
A(1;-4;7) B(5;6;-5)
|AB|=√(x₂-x₁)²+(y₂-y₁)²+(z₂-z₁)²=√(5-1)²+(6-(-4))²+((-5)-7)²=√16+100+144=√260=√4*65=2√65≈16,12
Похожие вопросы
Предмет: Английский язык,
автор: lolalzpro
Предмет: География,
автор: anastasia677832
Предмет: Русский язык,
автор: ekaterina8449
Предмет: Математика,
автор: katysnka